Design of Export Strategy for Roasted Beans Products to The Asean Market Using The Swot Method and The Use of Trade Map (Case Study: Pt Wahana Development Indonesia) - Hidayat, Faisal Ahmad; Jatnika, Dika (Riviera Publishing, 2024)
This research aims to analyze the potential of roasted coffee bean products and provide a strategy proposal for PT. Wahana Development Indonesia (Kopi Sarongge) to maximize sales by exporting roasted beans via the Trade Map website to ASEAN countries, particularly Singapore, Malaysia, and Thailand. The analysis methods employed include SWOT analysis, IFAS, EFAS, and strategy formulation using the TOWS matrix. Based on the processed data from the IFAS table, the IFAS value of 3.11 indicates that the Company possesses significant strengths. This suggests the Company has many internal advantages and capabilities. Furthermore, the EFAS table yielded a value of 2.73, indicating relatively favorable external conditions for the Company despite facing some challenges. In the TOWS matrix, the Company ranks 1st with an SO strategy, where it should leverage its reputation for high-quality coffee beans to meet the increasing demand in international markets, utilize competent human resources to explore the export-import sector, set competitive pricing to enhance competitiveness and attract international market interest, and utilize adequate production capacity to sell through various channels. This research was conducted to determine the strategies that the Company should employ to penetrate the ASEAN market.